Preventing insulin dependent diabetes mellitus: the environmental challenge. Diabetes Epidemiology Research International. (1987)
The epidemiology of insulin dependent diabetes mellitus was evaluated to determine the degree to which the disease results from environmental agents and therefore might be prevented. The results of research indicate that insulin dependent diabetes can be produced in animal models by environmental factors, there are major geographical variations in diabetes, certain populations have shown rapid changes in incidence over time, migrants appear to take on the risk of diabetes in their new country, and certain viruses and chemicals cause insulin dependent diabetes in humans. The results of genetic and epidemiological studies also show that at least 60% of insulin dependent diabetes world wide, and perhaps over 95%, is environmentally determined and thus potentially avoidable. It is concluded that the primary worldwide determinants of diabetes are environmental not immunogenetic and that identifying and altering the diabetogenic environmental factor(s) are likely to be more effective and less risky in preventing insulin dependent diabetes than current immunogenetic approaches.